Pengaruh Capital Intensity Dan Institusional Ownership Terhadap Tax Avoidance Dengan Profitabilitas Sebagai Pemoderasi (Studi Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2019-2022) - Nadia Priskila; Sri Yuni; Christina Fransiska; Oktobria Y. Asi; Ichsan Diarsyad; Iwan Christian (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of capital intensity and institutional ownership on tax avoidance with profitability as a moderating variable. This study uses a type of quantitative research using secondary data in the form of annual reports. In this study, the population is consumer goods industry companies listed on the IDX for the 2019-2022 period using a purposive sampling technique. Based on this technique, 31 companies were obtained with a span of 4 years of observation, so that 124 observation data were obtained. The data that has been obtained is then analyzed using the SPSS version 25 application. The results of this study indicate that capital intensity has no effect on tax avoidance and institutional ownership has a negative and significant effect on tax avoidance. Then profitability as a moderator is not able to moderate the effect between capital intensity on tax avoidance, while profitability is able to moderate the relationship between institutional ownership on tax avoidance. Suggestions for future researchers to be able to add other variables that affect tax avoidance and to be able to use other sector companies as objects of observation in order to be able to compare the results of one company's research with another.